PESANTREN SAINS DAN TEKNOLOGI UNTUK MENGIMBANGI PERSAINGAN GLOBAL - Sehat Sultoni Dalimunthe (IBDA` : Jurnal Kajian Islam dan Budaya, 2011)
Science dichotomy in the Islam is a long-standing theory and practice.If we read the history, Muslim authors excel in various fields of science.Therefore emerge the spirit of reform of Islamic education, includingthe education system of pesantren. Without mastering science andtechnology, Muslims will remain marginalized in the dynamics of modernsociety. By bringing science, technology, and information to the world ofpesantren, negative impacts can be fixed. When the third "ruler" was heldby the faithful, it is hoped the friendly and peaceful world.